Understanding religious attachment among christians seeking spiritually integrated psychotherapies: A mixed methods study. Issue 5 (2nd October 2021) - Currier, Joseph M.; Stevens, Laura T.; Hinkel, Hannah M.; Davis, Edward B.; Park, Crystal L.
Abstract: Objective: This mixed methods study aimed to understand ways of viewing and experiencing religious attachment among Christians in spiritually integrated psychotherapies. Method: In total, 190 Christian‐affiliated clients completed narrative responses about religious and parental attachment along with validated measures of spiritual and psychological functioning toward the start of treatment. Results: An inductive content analysis revealed ten ways in which clients were viewing and experiencing God. Although painful themes were expressed, clients more frequently discussed comforting themes related to religious attachment. Additional analyses demonstrated convergence with parental attachment and quantitative measures of spirituality and mental health. Conclusion: Religious attachment appears to primarily provide a sense of strength and comfort for Christians seeking care. Findings also indicate clients view and experience God in similar ways as their parents or caregivers. As such, assessing and affirming clients' faith may facilitate positive changes in how they view and experience themselves and others in treatment.